PENGARUH BOARD STRUCTURE DAN INTELLECTUAL CAPITAL DISCLOSURE TERHADAP FIRM PERFORMANCE - Amanda Wijaya; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aimed to examine the effect of board structure on intellectual capital disclosure and firm performance. Moreover, this study also aimed to know the indirect effect of board structure on firm performance through intellectual capital disclosure as the mediating variable. The sample used in this research was 41 banking companies listed on Indonesia Stock Exchange with observation years 2011-2016 and total observation 207 firm years. The data collected from the company’s annual report and Bloomberg then processed using WarpPLS 5.0.The results showed that board structure had positive influence on intellectual capital disclosure and firm performance and positive influence of intellectual capital disclosure on firm performance. This research also found that intellectual capital disclosure was not capable to mediate the influence of board structure on firm performance.